Strategi Penguatan Komitmen Terhadap Organisasi untuk Keberlanjutan Bisnis UKM Kuliner: Pendekatan Integratif berdasarkan Temuan Lapangan di Kota Bogor - Elizabeth, Roosganda; Notosudjono, Didik; Hamzah, Hamzah; Yusnita, Nancy; Moeins, Anoesyirwan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to formulate strategies for strengthening organizational commitment that support the sustainability of culinary SMEs in Bogor City. The research adopts a mixed method sequential explanatory approach, in which prior quantitative results are explored further through in-depth interviews. Informants include business owners, managers, and employees of various culinary SMEs. The findings reveal that organizational support, creative innovation, participative leadership, and human capital development are critical elements in sustaining employee loyalty and motivation. Based on thematic analysis and integration with the quantitative model, a strategic framework is developed involving reward systems, skills training, inclusive work culture, and employee empowerment. This study contributes to the development of an organizational commitment–based human resource strategy model within the informal sector.